Rekindled 《爱情左右》 - Lim, Alvin Eu Chian (Nanyang Technological University, 2020)
This FYP book is a compilation of all the processes the team went through from the start of the project till the end. It also contains write-ups of how each core team members manage their own department as well as the director and producer's final FYP reports.